2000
DOI: 10.1111/j.1749-6632.2000.tb06369.x
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Age of Onset of Alzheimer's Disease in Patients with Both the Transferrin C2 and Apolipoprotein E‐ɛ4 Alleles

Abstract: The etiology of Alzheimer's disease is now known to be multifactorial. The genetic factors transferrin C2 (TfC2) and apolipoprotein E epsilon 4 (ApoE-epsilon 4) have both been associated with Alzheimer's disease (AD). Transferrin is the carrier protein for iron in the blood, while ApoE is involved with the transport and redistribution of lipids. In the present study, the polymerase chain reaction (PCR) method was used to determine the frequency of both TfC2 and ApoE-epsilon 4 in 27 AD patients, 9 vascular deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…This variant occurs in high frequency in patients with AD compared with non-demented controls [157 -160]. It has also been shown that early onset of AD is observed in patients with both ApoE4 and TfC2 alleles [161]. Further, and that Al uptake occurs more in neurons of cortex and hippocampus, which are rich in Tf receptors [31].…”
Section: Cross-talk Between Genetic Susceptibility and Al In Admentioning
confidence: 99%
“…This variant occurs in high frequency in patients with AD compared with non-demented controls [157 -160]. It has also been shown that early onset of AD is observed in patients with both ApoE4 and TfC2 alleles [161]. Further, and that Al uptake occurs more in neurons of cortex and hippocampus, which are rich in Tf receptors [31].…”
Section: Cross-talk Between Genetic Susceptibility and Al In Admentioning
confidence: 99%
“…Of particular interest in this regard was to investigate the potential interactive role between age and the e4-allele, since the negative influences of the e4 allele on olfactory function and dementia prevalence are age-related (Li et al 2002;Olofsson et al in press;van Rensburg et al 2000). Also, given that a range of health conditions may have a negative impact on olfactory and cognitive functions, these factors were statistically controlled for.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of 679 amino acids folded into two domains, each of which contains a metal ion-binding site. Some studies have indicated that there is a correlation between a genetic variant of Tf, carrying a P570S mutation called TfC2, and AD [71][72][73]. Tf is N-glycosylated at Asn413 and Asn611, and, owing to heterogeneity in the glycan structures, several glycosylation variants exist.…”
Section: Tf and Glycosylationmentioning
confidence: 99%